YouTube and Schizophrenia: The Quality and Reliability of Information in the Age of Infodemics - Carolina Suárez-Llevat; Iván Herrera-Peco; Carlos Ruiz-Núñez; Álvaro Carmona-Pestaña; Raquel Romero-Castellano; Beatriz Jiménez-Gómez (Psychiatry International)
Background and Objectives: Schizophrenia is a significant public health issue, and YouTube has become an increasingly popular source of health information. This study aims to assess the quality and validity of YouTube videos about schizophrenia, focusing on the presence of scientific evidence and the role of healthcare professionals in content quality. Methods: A retrospective, cross-sectional observational study was conducted. One hundred videos in Spanish were selected using NodeXL Pro software, based on specific keywords and hashtags. The videos were categorized by content type and assessed using the DISCERN and Global Quality Scale [GQS] tools to evaluate quality and reliability. Results: Only 39% of the videos referenced scientific articles or technical documents. The videos created by healthcare professionals exhibited a higher quality and reliability. Significant differences were found in the DISCERN and GQS scores between the videos presenting personal opinions and those providing scientific information, favoring the latter. Conclusion: There is a prevalence of misinformation about schizophrenia on YouTube. To enhance the educational value of the platform and reduce misinformation risks, involving healthcare professionals in content creation and implementing control mechanisms is essential.